The Sea as a Representation of Male Domination in Emily Dickinson’s “I started Early – Took my Dog” - Thapa, Santosh (NPRC Journal of Multidisciplinary Research, 2025)
Background: Emily Dickinson’s poetry frequently engages with themes of nature, gender, and power. Her poem “I started Early – Took my Dog” is a compelling case study, where the sea operates as a potent metaphor for male domination, challenging the Romantic tradition of a feminine nature and instead portraying it as an aggressive, patriarchal force. Objective: This study aims to analyze how Dickinson symbolically represents the sea as an embodiment of male domination to critique patriarchal structures. It seeks to examine the poem’s figurative language, explore the speaker’s intuitive perception of masculinity and nature, and uncover the philosophical underpinnings of Dickinson’s resistance. Methods: The research employs a qualitative textual analysis of the poem, framed within a theoretical lens combining ecofeminism and deconstructive literary theory. This approach facilitates an examination of the intersections between gender, power, and nature, and the subversion of traditional binaries like male/female and dominance/submission. Findings: The analysis reveals that Dickinson constructs the sea as an intrusive masculine force, using vivid imagery and stylistic techniques (such as dashes and irregular meter) to convey themes of aggression and threat. The poem demonstrates a nuanced resistance to patriarchal control, destabilizing conventional power hierarchies. However, its ambiguous conclusion suggests a complex engagement with oppression, acknowledging its pervasive influence rather than presenting an overt triumph. Conclusion: In “I started Early – Took my Dog,” Dickinson successfully critiques patriarchal authority by reconfiguring the sea as a symbol of male domination. The poem asserts a defiant, though complex, stance against gendered oppression, using nature as a domain to explore and challenge societal power dynamics. Implication: This research underscores the enduring relevance of Dickinson’s work in feminist and ecofeminist discourse, highlighting her innovative use of nature symbolism to articulate a distinctly female experience of autonomy and intrusion. It contributes to scholarship by illuminating her subtle yet potent strategies of resistance.